NTPC, Tanda - Maheshwari, Sunil Kumar (London : Indian Institute of Management, Ahmedabad, 2024)
The Tanda unit of UPSEB is a distressed asset—dues to the power generator supplying UP—NTPC—are mounting. Finally, a resolution of debt is negotiated with the unit to be handed over to NTPC in place of the debt. The challenge for NTPC is to turn the plant around from a 20% PLF to break-even and finally, reach the NTPC standard of 90%. The sale is sensitive politically as well as from the Industrial Relations point of view. The power behemoth did not want an unmanageable situation so it marshalled its resources from other units. This was in January 2001 when the power sector in India was churning with reform. An experienced, hand-picked team was tasked for this delicate operation with the 19-to-90 mandate. The team was left free to analyse the situation on the ground, come up with a plan and execute it. As long as they could convince the Head Office of their plans, they had their backing—any short-term deviation had to be corrected so that the NTPC standard was maintained. In this, there was a typical corporate approach followed by the PSU. There were prior successful experiences of NTPC taking over units and turning them around. However, each situation is different—the external forces, the internal situation as well as persons vary from case to case. This case illustrates the issues in a corporate turnaround and how best practices are adopted with judicious flexibility. It also discusses how a culture of non-performance is converted into an environment of success with regard to technical as well as financial parameters. The entire gamut of change management through skilful organisation development is well exposed in this case making for good learning from "how not to manage" to "how to manage". The example of a continuous process utility is especially good for learning, as is the transition from state-run to corporate.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Corporate turnarounds -- India -- Case studies